The Demography of Youth in Developing Countries and its Economic Implications - Lam, David (World Bank, Washington, DC, 2012)
The number of young people is reaching unprecedented levels in most developing countries. In many countries, especially in East Asia and Latin America, youth populations are at or near their peak, and will decline in coming decades. In other countries, especially in Africa and South Asia, youth populations will continue growing for several decades. From an economic perspective, absolute numbers may be less important than the growth rate or relative size of youth cohorts. Growth rates and the ratio of youth to working-age population reached a peak in the 1970s or 1980s in most developing countries. The worst economic pressures of youth demography may have already occurred in many countries, although significant pressure will continue in Africa and South Asia.